Revisiting the returns to education during rapid structural and rural transformation in Thailand: A regression discontinuity approach - Upalat Korwatanasakul (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper estimates returns to schooling in Thailand, applying a regression discontinuity approach to the change in the compulsory schooling law in 1978. This law helped to enhance human capital investment on the eve of rapid structural transformation. The returns to schooling based on our instrumental variables estimation were around eight per cent, while ordinary least squares (OLS) overestimated such returns. Returns were higher in urban areas, service sectors, and underdeveloped northern regions. Our findings contrast sharply with recent studies exploiting similar institutional changes in developed countries, where OLS estimates underestimate returns to schooling, with the implication that former school dropouts tend to have higher returns than those who were already in school before the law changed. Ability bias is more likely to arise in developing countries, possibly because parents might be forced to keep only children with higher abilities in school, reinforcing inequality among children within the household.
Keywords: I20; I21; I25; I28; 330; returns to education; Mincer equation; ability bias; regression discontinuity; Thailand